The Influence Of Compensation And Work Motivation On Job Satisfaction Of Gojek Surabaya Drivers: Analysis of Factors Influencing Job Satisfaction Among Gojek Surabaya Drivers - Fiqri Istighfarul Haqi; Swasti, Ika Korika (Management Science Research Journal, 2024)
The development of the digital economy in Indonesia triggers a transformation in the labor sector, including application-based industries such as Gojek. Factors that influence driver job satisfaction include compensation and work motivation, while the reduction of compensation and lack of appreciation for driver performance often become issues. This research aims to analyze the influence of compensation and work motivation on job satisfaction among Gojek drivers Surabaya. This research uses a quantitative approach with data collected through questionnaires from 100 Gojek drivers Surabaya as the sample. The data analysis technique uses Partial Least Square (PLS) through the Smart PLS 4 program. Research results show that compensation, with the main aspect of incentives, contributes positively to job satisfaction. Work motivation also has a significant impact with the main indicator being recognition. These results indicate that the increase in compensation and work motivation plays an important role in enhancing the job satisfaction of Gojek drivers Surabaya. Keyword: Compensation, Gojek Drivers, Job Satisfaction, Work Motivation.